Optimalisasi Peran Perpustakaan dalam Meningkatkan Literasi Media Mahasiswa - Masruroh, Umi; Cahyono, Teguh Yudi (UNILIB : Jurnal Perpustakaan, 2025)
This research aims to explore the role of the library in improving students' media literacy at Universitas Negeri Malang through a qualitative descriptive approach. In an effort to understand this dynamic, we collected data through direct observation and in-depth interviews with students as well as library staff. The results showed that although the library has provided various media literacy programs and relevant resources, their effectiveness is still limited by several factors, including the lack of student participation and the low integration of media literacy programs into the academic curriculum. Furthermore, it was found that most students do not have adequate skills to critically analyze and evaluate information, which is due to the lack of socialization of the program as well as learning methods that are still theoretical without adequate practical application. Based on these findings, this study suggests the need for improved socialization strategies, the development of a more interactive and needs-based media literacy program, and closer collaboration between libraries and faculties to ensure media literacy becomes an integral part of higher education.